Life cycle cost and life cycle energy in zero-energy building by multi-objective optimization - Chen She; Rui Jia; Bei-Ning Hu; Ze-Kun Zheng; Yi-Peng Xu; Dragan Rodriguez (Energy reports, 2021)
The energy consumption in buildings is increasing, then, a new global multiple-objective optimization method for zero-energy buildings with the comprehensive assessment method is used in this study. The applied optimization design methods for renewable energy systems are the multiple-objective optimization by Enhanced Archimedes Optimization Algorithm (EAOA) on the original design for energy costs and energy optimal models. The Hybrid Gray Multiple-Level Comprehensive Assessment Method (HGMLCAM) is utilized to the optimal model including the solar energy use efficacy, energy conservation, economic and social factors. By the selected decision based on the global optimal model, the best solution is presented. For designing the practical building, the defined solution can be useful for the architects and decision-makers. Consequently, a multiple-objective design for a building located in Shanghai, in China, is studied. Based on the results, it can be concluded that the presented method is efficient to make decisions.